Modeling stream temperature in the Anthropocene: An earth system modeling approach. (29th October 2015) - Li, Hong‐Yi; Ruby Leung, L.; Tesfa, Teklu; Voisin, Nathalie; Hejazi, Mohamad; Liu, Lu; Liu, Ying; Rice, Jennie; Wu, Huan; Yang, Xiaofan
Abstract: A new large‐scale stream temperature model has been developed within the Community Earth System Model (CESM) framework. The model is coupled with the Model for Scale Adaptive River Transport (MOSART) that represents river routing and a water management model (WM) that represents the effects of reservoir operations and water withdrawals on flow regulation. The coupled models allow the impacts of reservoir operations and withdrawals on stream temperature to be explicitly represented in a physically based and consistent way. The models have been applied to the Contiguous United States driven by observed meteorological forcing. Including water management in the models improves the agreement between the simulated and observed streamflow at a large number of stream gauge stations. It is then shown that the model is capable of reproducing stream temperature spatiotemporal variation satisfactorily by comparing against the observed data from over 320 USGS stations. Both climate and water management are found to have important influence on the spatiotemporal patterns of stream temperature. Furthermore, it is quantitatively estimated that reservoir operation could cool down stream temperature in the summer low‐flow season (August–October) by as much as 1∼2°C due to enhanced low‐flow conditions, which have important implications to aquatic ecosystems. Sensitivity of the simulated stream temperature to input data and reservoir operation rules used in the WM model motivates future directions to address some limitations in the current modeling framework. Key Points: A new stream temperature coupled to the Community Land Model Human impacts in terms of reservoir regulation and surface water withdrawal Cooling effect of reservoir operation on summer stream temperature quantified